Breakthrough Supply Chains - Gopal, Christopher (McGraw-Hill Education, 2023)
A timely guide to rethinking and reinventing supply chains with breakthrough thinking to benefit your organization, the economy, and the world Major global events have brought to the forefront the impact of supply chains on everything from the success of companies and the health of individuals to global prosperity. As global business and geopolitical conditions change radically, it is imperative that supply chain strategies and operations transform to thrive in a volatile environment. Leaders have come to recognize the critical importance of resilience, agility, flexibility, and assurance of supply. Breakthrough Supply Chains provides a comprehensive view of end-to-end supply chains and dispels the common myths about them. It provides "breakthrough thinking" principles that address critical topics for enterprise and public policy: How supply chains have enabled profitable and beneficial growth in the evolving world The evolution of "the new customers" and what they demand The critical success factors for managing demand and supply in a complex and risky world Information, data, governance, analytics and measurements that guide strategic choices Resilience, risk, and supply assurance Sustainable supply chains and the environment Whether you are a business executive, manager, government agency leader, or member of the interested public, Breakthrough Supply Chains reinvents the supply chain with far-reaching effects. This is your go-to guide.